Ocular markers of microangiopathy and their possible association with cardiovascular risk in patients with systemic inflammatory rheumatic diseases: a systematic review - Sturm, Bengta; Zang, Anna-Lena; Stingl, Julia; Hasseli-Fräbel, Rebecca; Fanouriakis, Antonis; Schwarting, Andreas; Geber, Christian; Weinmann-Menke, Julia; Alhaddad, Mohammed; Triantafyllias, Konstantinos (Frontiers in Immunology, 2025)
Individuals with autoimmune rheumatic diseases (ARDs) are at a higher cardiovascular (CV) risk due to systemic inflammation, which contributes to endothelial dysfunction, atherosclerosis, and structural changes in the vessel walls. Along with traditional CV risk factors like dyslipidaemia, arterial hypertension, obesity, and impaired glucose metabolism, these patients have a severe prognosis with higher CV morbidity and mortality rates. To date, there is limited data on the optimal CV screening methods for individuals with ARDs, as conventional risk algorithms may underestimate the influence of chronic inflammation. In comparison to macrovascular assessment methods, such as carotid-femoral pulse wave velocity and carotid sonography, microvascular changes, which may precede macrovascular disease, have been less investigated. The ocular microvasculature reflects systemic vascular health and can reveal early signs of CV disease. Changes in retinal vessels have been linked to an increased long-term risk of CV mortality and ischemic stroke in longitudinal studies of the general population, such as the large Atherosclerosis Risk in Communities (ARIC) study. Additionally, various cross-sectional and follow-up studies in patients with ARDs have demonstrated associations between ocular vessel changes, traditional CV risk scores, and disease-related characteristics, suggesting a potential role for ocular assessments in CV risk screening. In this review work, research from 26 studies retrieved from the PubMed and Web of Science databases has been highlighted. Herein, we evaluate the techniques of retinal vessel analysis (RVA), optical coherence tomography angiography (OCT-A), spectral domain-OCT (SD-OCT), and retrobulbar color Doppler. Specifically, we examine the available data on their associations with key CV risk factors, systemic inflammation, surrogate CV markers, and traditional CV risk scores. Furthermore, we discuss their potential diagnostic value in both ARDs and the general population. Despite current limitations, such as small sample sizes and methodological heterogeneity, initial findings suggest that these techniques may provide valuable insights into microangiopathy and CV risk. Future research should focus on larger, well-designed longitudinal studies to establish their prognostic value and potential integration into clinical practice.